Dielectric Coating‐Induced Absorption Enhancement in Si Nanowire Junctions. Issue 1 (10th November 2014) - Solanki, Amit; Gentile, Pascal; Boutami, Salim; Calvo, Vincent; Pauc, Nicolas
<x xml:space="preserve">Abstract</x> The efficient photon management in nanowires coupled with tunable absorption can provide a significant advancement in the current solar cell technology. Adding a shell on the nanowire (NW) offers an extra degree of freedom for tailoring the NW absorption. Calculations are performed to study the shell‐induced changes in the core absorption of an ideal Si nanocylinder after enclosing it with conformal dielectrics of different thicknesses and permittivities. The calculation shows that coating the Si nanowires with nonabsorbing or weakly absorbing dielectric shells can significantly improve the mean spectral absorption efficiency of the Si core for optimized thickness and extinction. Experimental data are brought from a neighboring system consisting of individual NW junctions sandwiched between an oxidized planar Si substrate and a top‐deposited oxide layer. The measured absorption spectra show a good agreement with the theoretical spectra, with a mean spectral absorption enhancement after oxide coating as high as 5.7 in axial junctions, exceeding its theoretical counterpart that is limited to ≈1.5. Coating the nanowires with an optimized oxide shell provides a new approach to significantly enhance the light harvesting in nanowires and will lead to more efficient photovoltaics.